Association of P2Y12 Gene Promoter DNA Methylation with the Risk of Clopidogrel Resistance in Coronary Artery Disease Patients. (18th March 2014) - Su, Jia; Li, Xiaojing; Yu, Qinglin; Liu, Yahui; Wang, Yaqing; Song, Haojun; Cui, Hanbin; Du, Weiping; Fei, Xiaohong; Liu, Junsong; Lin, Shaoyi; Wang, Jian; et al.
Abstract : Background . Clopidogrel inhibits the ADP receptor P2Y12 to keep down the platelet aggregation. The goal of our study is to investigate the contribution of P2Y12 promoter DNA methylation to the risk of clopidogrel resistance (CR). Methods . The platelet functions were measured by the VerifyNow P2Y12 assay. Applying the bisulfite pyrosequencing technology, DNA methylation levels of two CpG dinucleotides on P2Y12 promoter were tested among 49 CR cases and 57 non-CR controls. We also investigated the association among P2Y12 DNA methylation, various biochemical characteristics, and CR. Result . Lower methylation of two CpGs indicated the poorer clopidogrel response (CpG1, P = 0.009 ; CpG2, P = 0.022 ) in alcohol abusing status. Meanwhile CpG1 methylation was inversely correlated with CR in smoking patients (P = 0.026 ) and in subgroup of Albumin < 35 (P = 0.002 ). We observed that the level of DNA methylation might be affected by some clinical markers, such as TBIL, LEVF, Albumin, AST. The results also showed that the quantity of stent, fasting blood-glucose, and lower HbAC1 were the predictors of CR. Conclusions . The evidence from our study indicates that P2Y12 methylation may bring new hints to elaborate the pathogenesis of CR.